Dead in Their Vaulted Arches a Flavia de Luce novel - Bradley, C. Alan (New York Delacorte Press, 2014)
"On a spring morning in 1951, eleven-year-old chemist and aspiring detective Flavia de Luce gathers with her family at the railway station, awaiting the return of her long-lost mother, Harriet. Yet upon the train's arrival in the English village of Bishop's Lacey, Flavia is approached by a tall stranger who whispers a cryptic message into her ear. Moments later, he is dead, mysteriously pushed under the train by someone in the crowd. Who was this man, what did his words mean, and why were they intended for Flavia? Back home at Buckshaw, the de Luces' crumbling estate, Flavia puts her sleuthing skills to the test. Following a trail of clues sparked by the discovery of a reel of film stashed away in the attic, she unravels the deepest secrets of the de Luce clan, involving none other than Winston Churchill himself. Surrounded by family, friends, and a famous pathologist from the Home Office--and making spectacular use of Harriet's beloved Gypsy Moth plane, Blithe Spirit--Flavia will do anything, even take to the skies, to land a killer. Acclaim for Alan Bradley's beloved Flavia de Luce novels, winners of the Crime Writers' Association Debut Dagger Award, Barry Award, Agatha Award, Macavity Award, Dilys Winn Award, and Arthur Ellis Award: 'If ever there were a sleuth who's bold, brilliant, and, yes, adorable, it's Flavia de Luce.'--USA Today ; 'Irresistibly appealing.'--The New York Times Book Review, on A Red Herring Without Mustard; 'Original, charming, devilishly creative.'-- Bookreporter, on I Am Half-Sick of Shadows; 'Delightful and entertaining.'--San Jose Mercury News, on Speaking from Among the Bones"--
"Bishop's Lacey is never short of two things: Mysteries to solve and pre-adolescent detectives to solve them. In this New York Times bestselling series of cozy mysteries, young chemist and aspiring detective Flavia de Luce once again brings her knowledge of poisons and her indefatigable spirit to solve the most dastardly crimes the English countryside has to offer and, in the process, comes closer than ever to solving her life's greatest mystery--her mother's disappearance.."--
Keywords: De Luce, Flavia (Fictitious character); Girls -- England; Murder -- Investigation; Family secrets; Fiction / Mystery & Detective / General; Fiction / Thrillers; Fiction / Historical; Mystery fiction